PENERAPAN MEDIA KARTU BERGAMBAR DIGITAL UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENGIDENTIFIKASI JENIS EKOSISTEM HUTAN DULAMAYO MATA PELAJARAN MULOK KELAS V - Rawida M.T; Razak H. Umar; Inka Rizkyani Akolo (Al-mujahidah, 2026)
This study aims to improve students' ability to identify the types of Dulamayo Forest ecosystems through the application of digital picture card media in Local Content (Mulok) subjects in grade V of SDN 16 Limboto. The problem in this study is the low ability of students to recognize and understand the types of ecosystems found in Dulamayo Forest due to the lack of use of interesting and interactive learning media in the teaching and learning process. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects were 17 grade V students of SDN 16 Limboto. Data collection techniques were carried out through observation, tests, and documentation. The data obtained were analyzed descriptively quantitatively and qualitatively. The results of the study indicate that the application of digital picture card media can improve students' ability to identify the types of Dulamayo Forest ecosystems. This can be seen from the increase in student learning outcomes in each cycle. In the initial stage, the level of student learning completeness was still low, then increased in cycle I, and increased significantly in cycle II until it reached the predetermined success indicators. In addition, the use of digital picture card media also increases students' interest, attention, and activeness in the learning process.